Самоорганізація волонтерських ініціатив під час подій на Майдані 2013–2014 рр. - Прохорова, Анна; Prokhorova, Anna (Східноєвропейський національний університет імені Лесі Українки, 2017)
Ґрунтуючись на масиві з 400 глибинних інтерв’ю, отриманих у межах проектів «Майдан. Свідчення» та «Майдан. Медична допомога», досліджено процеси створення й функціонування самоорганізованих волонтерських ініціатив під час подій Майдану 2013–2014 рр. та виокремлено їхні структурні характеристики та особливості. Виявлено дві основні структурні характеристики самоорганізованих волонтерських ініціатив Майдану, що давали їм змогу діяти ефективно й швидко: горизонтальна структура утворення та функціональна спеціалізація її членів. Серед особливостей утворення й функціонування волонтерських ініціатив Майдану зазначено спонтанне та швидке створення в періоди загострення ситуації, виконання одних і тих самих функцій різними організаціями, активну комунікацію через Інтернет та соціальні мережі, наявність подібних статусних характеристик в ініціаторів організацій, залучення значних людських і матеріальних ресурсів до власної діяльності. The article studies the processes of development and functioning of self-organized volunteer initiatives during the events of the Maidan (2013–2014) and their structural characteristics and peculiarities relying on the pool of 400 in-depth interviews, gathered at the projects Maidan. Testimonies and Maidan. Medical source. It is shown that self-organization of the volunteer initiatives arose spontaneously and rapidly as a response to new emerging needs that appeared during the periods of aggravation of the situation. The two main structural characteristics of the self-organized volunteer initiatives of the Maidan that allowed them to act quickly and effectively were their horizontal character and functional specialization of their members. Different organizations of the Maidan performed the same functions, partly because of the complexity of coordination during the periods of intensive work, and partly in view of diversifying the risks. Another peculiarity of these initiatives consisted in active communication through the Internet and social networks both among activists and with all those who wished to help. Volunteer organizations of the Maidan were initiated by people of a certain type: young, educated, active, middle class. One more peculiarity of self-organized volunteer initiatives that have been analyzed, is that they managed to attract significant resources to their activities, both material and human.
Self-Organization of the Volunteer Initiatives During the Events of the Maidan 2013–2014
Keywords: Майдан; волонтерська активність; самоорганізація; глибинні інтерв’ю; Maidan; volunteering activities; self-organisation; depth interview